ANALISIS PELAKSANAAN SISTEM INFORMASI REKAM MEDIS BAGIAN PENDAFTARAN RAWAT JALAN DI RSUD PANEMBAHAN SENOPATI BANTUL TAHUN 2019 - Jamroni; Farizah (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
Background: Medical Record Information System is a very vital requirement for a medical institution. In order to speed up the provision of medical record information services to almost the entire hospital using the medical record information system including the Panembahan General Hospital, Senopati Bantul. Based on the results of a preliminary study conducted on the twenty-first of September 2018 on one of the patients who were waiting in the outpatient registration section with an average waiting time of 11.22 minutes, this complaint was confirmed by 2 other patients who were lining up with these patients. Purpose: Analyze the Implementation of Medical Record Information Systems in the Outpatient Registration Section at Panembahan Senopati Hospital Bantul. Method: This study uses qualitative research methods. This research was carried out by means of source triagulation techniques. This research was carried out in the Outpatient Registration section of Panembahan Senopati Hospital Bantul. Results: The results of the study show that the Analysis of the Medical Record Information System Implementation in Outpatient Registration Section at Panembahan Senopati Hospital Bantul is human resources, facilities and infrastructure, software flow and hardware conditions. Conclusion: Human resources, facilities and infrastructure, software flow and hardware conditions affected by network errors and applications that are down.